2017
DOI: 10.22146/ijc.24895
|View full text |Cite
|
Sign up to set email alerts
|

<i>Ab Initio</i> Study of Proton Transfer and Hydration in Phosphorylated Nata de Coco

Abstract: This research aims to calculate energetics parameters, hydrogen bonding, characteristics local hydration, and proton transfer in phosphorylated nata de coco (NDCF) membrane using ab initio method. The minimum energy structure of NDCF membranes and the addition of n water molecules (n = 1-10) Calculation of the rotational energy at the center of C-O indicates that the pyranose ring structure, with a maximum barrier energies of~12.5 J/mol, is much more flexible than the aromatic backbones of sulfonated poly(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Dissociation of alginic acid molecules happened as the water molecule number increased, which was presented with the longer bond lengths of O7-H39 and O11-H43, which were up to 1 Å. The same results were also reported by previous researchers [ 41 , 42 ]. On the other hand, Table 2 showed that sodium’s hydration process of carboxylic sodium salt occurred in addition to two water molecules, which was proved by the fact that the distance between O and Na was longer than 2.3 Å.…”
Section: Resultssupporting
confidence: 85%
“…Dissociation of alginic acid molecules happened as the water molecule number increased, which was presented with the longer bond lengths of O7-H39 and O11-H43, which were up to 1 Å. The same results were also reported by previous researchers [ 41 , 42 ]. On the other hand, Table 2 showed that sodium’s hydration process of carboxylic sodium salt occurred in addition to two water molecules, which was proved by the fact that the distance between O and Na was longer than 2.3 Å.…”
Section: Resultssupporting
confidence: 85%
“…The adsorption energy values classified the interaction as a medium hydrogen bond interaction because they were in the range of −4 kcal mol −1 < adsorption energies < −20 kcal mol −1 . 66,67 Secondly, the adsorption distance of the complex molecules was calculated by the distance between the N atom (in the NH 2 -Cdots) and the H atom from H 2 O 2 . The adsorption distance of the complex molecules in the C–N⋯H hydrogen bond interaction of 1-com is smaller than that of 2-com and 3-com.…”
Section: Resultsmentioning
confidence: 99%
“…All adsorption distances were in the range of 1.5 Å < adsorption distances < 2.2 Å, and classified the interaction as a medium hydrogen bond interaction. 66,67 Finally, the Mulliken atomic charges 68 of H 2 O 2 before and after adsorption were used to measure the charge transfer of H 2 O 2 molecules adsorbed on the NH 2 -Cdots; a negative Q t value suggests electron accumulation of the H 2 O 2 . 69,70 The charge transfer was highest for 1-com compared with 2-com and 3-com.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the analysis of proton transfer through the interaction of NDCS with n H2O, which is by adding n water molecules (n = 1,2, ... 10) gradually to the NDCS membrane into the representative structural model. The method used is the DFT method with functional B3LYP and 6-311G (d) basis set and then corrected for zero point energy (ZPE) and BSSE as has been done by Wang and Paddison on sulfonated poly phenylene and Rahmawati et al on NDCP [9,15]. This is done to determine the characteristics of hydration, dissociation and transfer of protons in the membrane.…”
Section: Energy Calculationmentioning
confidence: 99%